2011
DOI: 10.3989/scimar.03313.21b
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the purple dye murex, <i>Bolinus brandaris</i> (Gastropoda: Muricidae), marked and released in a semi-intensive fish culture earthen pond

Abstract: SUMMARY: The present study reports the growth rate of the purple dye murex, Bolinus brandaris (Gastropoda: Muricidae), estimated from mark-recapture experiments. A total of 1067 specimens (shell length = 43.4±8.1 mm, range = 14.6−78.4 mm) were marked with Dymo ® tape tags and released in a semi-intensive fish culture earthen pond. After a period at liberty ranging from almost two months to around two years, 288 individuals were recaptured (shell length = 67.4±6.2 mm, range = 45.3−88.6 mm), which corresponded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Indeed, previous pilot studies focused on establishing the technical and economical feasibility of rearing B. brandaris (e.g. Ramón & Flos 2001, Ramón et al 2005, Vasconcelos et al 2012. However, despite the efforts of some researchers to achieve spawning of B. brandaris in captivity, this task has proved unsuccessful until now.…”
Section: Vasconcelos Et Al: Reproductive Cycle Of Bolinus Brandarismentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, previous pilot studies focused on establishing the technical and economical feasibility of rearing B. brandaris (e.g. Ramón & Flos 2001, Ramón et al 2005, Vasconcelos et al 2012. However, despite the efforts of some researchers to achieve spawning of B. brandaris in captivity, this task has proved unsuccessful until now.…”
Section: Vasconcelos Et Al: Reproductive Cycle Of Bolinus Brandarismentioning
confidence: 98%
“…Ease of capture, sedentary lifestyle, aggregation for breeding and spawning, deposition of collective spawns and intracapsular development (Ramón & Flos 2001, Vasconcelos et al 2008a, limit the potential of dispersal and intrinsic ability to quickly recolonise over-harvested areas. Life history characteristics of B. brandaris, such as relatively slow growth (Ramón & Flos 2001, Vasconcelos et al 2012) and first sexual maturity reached ~55 mm SL (K. Elhasni, pers. comm.)…”
Section: Discussionmentioning
confidence: 99%
“…In general, the correlation coefficients of the morphometric relationships were slightly higher in the banded murex than in the purple dye murex, indicating greater morphological plasticity and higher variability in shell shape in B. brandaris compared with H. trunculus . Studies on the absolute growth revealed that both species display high inter-individual variability in growth rates, that extend from the embryonic, hatchling and juvenile stages (Vasconcelos et al , 2004; Lahbib et al , 2010) until the adult life phase (Vasconcelos et al , 2006c, 2012a, c), which might also induce variability in shell shape and relative growth of H. trunculus and B. brandaris . Higher variability in shell shape of B. brandaris compared with H. trunculus could also be due to the fact that shells of B. brandaris are thinner, weaker and more ornamented than those of H. trunculus , thus more fragile and susceptible to damage (especially in the siphonal canal and in the outer lip of the shell aperture), which might ultimately affect shell proportions and relative growth.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports data gathered and compiled in multidisciplinary tasks performed with H. trunculus and B. brandaris from the Ria Formosa lagoon (southern Portugal) (Figure 1) during several years, including experimental fishing surveys (Vasconcelos et al ., 2008a), marking-recapture-release experiments (Vasconcelos et al , 2006c, 2012c) and monthly biological sampling for diverse purposes (e.g. Vasconcelos et al , 2006a, b, 2007, 2008b, c, 2009, 2011, 2012b).…”
Section: Methodsmentioning
confidence: 99%
“…In muricids, intraspecific predation (cannibalism) has been shown to take place in living gastropods (e.g., Paine, 1966;Spanier, 1986;Rilov et al, 2004;Vasconcelos et al, 2012), although very little information is available for the snail T. geversianus. Osorio (2002) first reported cannibalism in T. geversianus under aquarium conditions, and more recently Cumplido et al (2011), studying the embryological development of this species, observed drilling attempts in a prehatching embryo of T. geversianus, thus also suggesting cannibalism.…”
Section: Muricid Gastropods and Cannibalismmentioning
confidence: 99%